Social Dynamics the Role of Social Media in Shaping Collective Identity - Khaeriyah Khaeriyah; Nurasia Natsir (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2024)
This research explores the role of social media in shaping collective identity among users in contemporary society. By employing a qualitative methodology that includes in-depth interviews and content analysis, the study investigates how individuals create and share content that reinforces their group affiliations and fosters a sense of belonging. The findings reveal that social media platforms serve as vital spaces for community building, where users share personal narratives and visual content, and engage in discussions that highlight shared values and experiences. Key themes identified include the impact of different content types on identity formation, the influence of community leaders and influencers, and the significance of intersectionality in shaping collective identities. While positive interactions on social media can strengthen group cohesion, negative experiences and the prevalence of echo chambers can lead to fragmentation and exclusion. This research underscores the dual nature of social media as both a tool for connection and a potential source of division. Ultimately, the study contributes valuable insights into the complexities of identity formation in the digital age and emphasizes the need for inclusive and supportive online environments. As social media continues to evolve, understanding these dynamics is essential for fostering social cohesion and empowering communities in an increasingly interconnected world.